Avaliação da estabilidade oxidativa do biodiesel de pinhão manso (Jatropha curcas L.) e suas misturas ao diesel - Brasilino, Maria das Gracas Azevedo (2010)
Jatropha curcas L. as a raw to produce biodiesel presents a promising alternative because of the perennial production of its fruits and a high oil concentration on its seeds. The mechanical extraction of the oil yielded 38% while the chemical extraction yielded 44.8% but the oil chemically extracted presented a higher acidity index, in relation to the mechanical extracted oil, factor that interferes in the transesterification reaction. The chromatographic data showed higher concentration of oleic acid (C 18:1) with 35,89% and linoleic acid (C 18:2) with 44,45%. The ethyl biodiesel was obtained through alcaline transesterification (KOH) and the 5%, 10% and 20% (m/m) biodiesel/diesel mixtures were prepared and then submitted to storage for 120 days, at room temperature. The results of RMN 1H and medium infrared characterized the ethyl biodiesel and its mixtures (B5, B10 and B20). The oxidative behavior of ethyl biodiesel and its mixtures were monitored through UV-Visible spectroscopy. The PetroOXY (OITB100= 52, 48, 35, 28 min) and P-DSC (HPOITB100= 41,30; 22,63; 7,72 min) techniques monitored the pure biodiesel s oxidative process and the results obtained indicate that oxidation occurred through the long period of storage. The cold hydrodynamic and flow properties confirmed the oxidative process, where was observed a slightly increase in viscosity, however the mixtures, although the biodiesel influence, after 120 days of storage kept into the required parameters by ANP regulations and consequently into commercialization conditions.